2022
DOI: 10.3390/cells12010030
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Adipose-Derived Regenerative Cells Isolated from Lipoaspirate Using a Point of Care System Does Not Depend on the Subject’s Individual Age, Sex, Body Mass Index and Ethnicity

Abstract: Uncultured, unmodified, autologous, adipose-derived regenerative cells (UA-ADRCs) are a safe and effective treatment option for various musculoskeletal pathologies. However, it is unknown whether the composition of the final cell suspension systematically varies with the subject’s individual age, sex, body mass index and ethnicity. UA-ADRCs were isolated from lipoaspirate from n = 232 subjects undergoing elective lipoplasty using the Transpose RT system (InGeneron, Inc.; Houston, TX, USA). The UA-ADRCs were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Adipose tissue-derived stem and regenerative cells can be isolated and administered in large numbers at the "point of care" without cell expansion/culturing [23]. These nonengineered cells also lead to high clinical safety and efficacy [24,25,26] Our data suggest an initial anti-inflammatory impact of the cells used. We also clinically observed an acute anti-inflammatory effect of the ADSCs, evidenced by the first clinical improvement often seen already 48 hours after treatment.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Adipose tissue-derived stem and regenerative cells can be isolated and administered in large numbers at the "point of care" without cell expansion/culturing [23]. These nonengineered cells also lead to high clinical safety and efficacy [24,25,26] Our data suggest an initial anti-inflammatory impact of the cells used. We also clinically observed an acute anti-inflammatory effect of the ADSCs, evidenced by the first clinical improvement often seen already 48 hours after treatment.…”
Section: Discussionmentioning
confidence: 78%
“…Consequently, local tissue damage can be treated by injecting stem cells at the site needing repair. Clinical applications have shown that tissue of all three germ lines can be treated with stem cells [2,25,26]. In degenerative diseases of joints, damage to functional tissue induces an inflammatory process, resulting in pain.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue-derived stem and regenerative cells can be isolated and administered in large numbers at the “point of care” without cell expansion/culturing [ 26 ]. These non-engineered cells also lead to high clinical safety and efficacy [ 20 , 21 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, local tissue damage can be treated by injecting stem cells at the site needing repair. Clinical applications have shown that tissue of all three germ lines can be treated with stem cells [ 15 , 20 , 21 ]. In degenerative diseases of joints, damage to functional tissue induces an inflammatory process, resulting in pain.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, all the subjects enrolled in the former study [12] suffered from a sPTRCT of the supraspinatus tendon at baseline, had not responded to physical therapy treatments for at least six weeks, and were randomly assigned to receive either a single injection of an average 11.4 × 10 6 UA-ADRCs (in 5 mL liquid; mean cell viability: 88%) (n=11; modified intention-to-treat (mITT) population) (hereafter: UA-ADRCs group) or a single injection of 80 mg of methylprednisolone (40 mg/mL; 2 mL) plus 3 mL of 0.25% bupivacaine (n=5 in the former study [12]; n=4 in the present study; mITT population) (hereafter: corticosteroid group). The UA-ADRCs were isolated from lipoaspirate using the Transpose RT system (InGeneron, Houston, TX, USA) [15,20]. One subject in the corticosteroid group experienced progression of sPTRCT into a symptomatic, full-thickness rotator cuff tear during the former study [12] and was therefore not enrolled in the present study.…”
Section: Methodsmentioning
confidence: 99%